Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
SPE Europec/Eage Annual Conference 2012
DOI: 10.2118/154429-ms
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Characterization Through Rate Correlation Analysis

Abstract: Statistical correlations in flowrate fluctuations between wells from many fields appear to bear out the expectation that the hydraulic conductivities of faults and fractures in reservoirs can be influenced by geomechanical perturbations due to production operations: the fluctuations are characterised by high correlations over very large separation distances between wells; and those correlations appear to be stress-related and fault-related. An entirely separate relationship derived from observations in multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Permeability changes are related to dilatation, or compression In the discussion about factors controlling the porosity and permeability of reservoirs, it is important to call once more the influence of mechanical status of an orogen on fractures and fluid flow [15]. The general structure of the reservoir and its environment is on the verge of mechanical failure [56]. Taking this into consideration, the bulk permeability of rock is influenced by changing stresses that are induced by the development of a HC reservoir in production.…”
Section: Factors Controlling Porosity and Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Permeability changes are related to dilatation, or compression In the discussion about factors controlling the porosity and permeability of reservoirs, it is important to call once more the influence of mechanical status of an orogen on fractures and fluid flow [15]. The general structure of the reservoir and its environment is on the verge of mechanical failure [56]. Taking this into consideration, the bulk permeability of rock is influenced by changing stresses that are induced by the development of a HC reservoir in production.…”
Section: Factors Controlling Porosity and Permeabilitymentioning
confidence: 99%
“…Permeability changes are related to dilatation, or compression of fractures, or faults, or new fractures in previously intact rock. Heffer [56] suggested that shear failure is a main factor controlling such changes.…”
Section: Factors Controlling Porosity and Permeabilitymentioning
confidence: 99%
“…Many waterfloods have relatively long fractures caused by thermal effects, pressure depletion (poroelastic) or plugging effects [1][2][3][4][5][6][7][8][9][10][11][12][13] . These fractures may be beneficial in that they help injectivity and injection rates.…”
Section: Introductionmentioning
confidence: 99%